Executive charisma - Benton, D. A. (Debra A.) (New York : McGraw-Hill, 2003)
An executive development coach offers managers a six-step program for developing executive charisma, self-confidence, style, composure, and leadership skills.
Be the first to initiate -- Expect and give acceptance to maintain esteem -- Ask questions and ask favors -- Stand tall, straight, and smile -- Be human, humorous, and touch -- Slow down, shut up, and listen -- Completing the puzzle.
Includes index.
Keywords: Executive ability; Executives -- Conduct of life; Executives; Charisma (Personality trait).; Communication in management; Charisma (Personality trait